Effects of land use and insecticides on natural enemies of aphids in cotton: First evidence from smallholder agriculture in the North China Plain - Ke Zhou; Jikun Huang; Xiangzheng Deng; Werf, A.W. van der; Zhang, Wei; Yanhui Lu; Kongming Wu; Feng Wu (Elsevier, 2014)
Studies conducted in the USA and Europe have shown that diverse landscapes in general support greater natural enemy abundance. No quantitative evidence on the relationship between land use diversity and natural enemies has been reported from developing countries, where fields and farms are much smaller than in modernized agriculture in the west, and where insecticide use is often high and indiscriminate. This paper examines the effects of land use and farmers’ insecticide application on natural enemies of aphids in cotton production, based on a unique dataset that links household and cotton field surveys to a detailed assessment of land uses in the landscapes surrounding the cotton fields in the North China Plain (NCP), a major grain and cotton production region in China. Our results show that, in the NCP where farms are small and landscape is dominated by a few crops, Shannon or Simpson land use diversity index is not a good indicator for explaining the relationship between land use and densities of aphid natural enemies. Instead, the types and proportions of cropland habitat mattered. Landscapes with more maize and grassland have higher ladybeetle populations in cotton fields. Farmers’ pest management practices such as the amount and timing of insecticide use significantly affect ladybeetle densities. These results imply that there is a need to recognize the potential positive role of cropland use in pest management and call for more judicious insecticide use strategies by smallholder farmers in the North China Plain.